A Bibliometric Analysis of Asset-Backed Securities in Structured Finance - Judijanto, Loso (West Science Accounting and Finance, 2025)
This study presents a comprehensive bibliometric analysis of the sustainable finance research landscape using data exclusively from the Scopus database and visualized through VOSviewer. By examining co-occurrence patterns, author networks, and international collaborations, the study uncovers major themes, influential contributors, and temporal developments in the field. The analysis identifies "asset-backed securities," "financial crisis," and "structured finance" as central topics, with shifts over time toward innovation-focused terms such as "liquidity" and "security design." Key scholars and intellectual clusters are mapped, highlighting interdisciplinary and geographically diverse contributions, with the United States emerging as the dominant research hub. Despite the robust scholarly output, gaps remain in the coverage of emerging financial instruments, methodological diversity, and institutional collaboration. The findings offer valuable insights for academics, policymakers, and practitioners seeking to understand the evolving dynamics and future directions of sustainable finance research.